2017
DOI: 10.3748/wjg.v23.i32.5962
|View full text |Cite
|
Sign up to set email alerts
|

Real time endoscopic ultrasound elastography and strain ratio in the diagnosis of solid pancreatic lesions

Abstract: AIMTo evaluate the accuracy of the elastography score combined to the strain ratio in the diagnosis of solid pancreatic lesions (SPL).METHODSA total of 172 patients with SPL identified by endoscopic ultrasound were enrolled in the study to evaluate the efficacy of elastography and strain ratio in differentiating malignant from benign lesions. The semi quantitative score of elastography was represented by the strain ratio method. Two areas were selected, area (A) representing the region of interest and area (B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
2
27
0
3
Order By: Relevance
“…We found a cut-off point of 4.55, which had specificity, sensitivity, PPV, NPV, and accuracy of 94.7%, 96.9%, 98.9%, 85.7%, and 96.5%, respectively. This was similar to the results of the study by Okasha and colleagues [11], who reported a cut-off point of 3.8, which had NPV, sensitivity, and accuracy of 86%, 99%, and 96%, respectively, but lower specificity and PPV of 53% and 84%, respectively. Kongkam et al [12] also reported a cut-off point of 3.17, which had lower specificity, sensitivity, PPV, NPV, and accuracy of 66.7%, 86.2%, 89.3%, 60%, and 81.6%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…We found a cut-off point of 4.55, which had specificity, sensitivity, PPV, NPV, and accuracy of 94.7%, 96.9%, 98.9%, 85.7%, and 96.5%, respectively. This was similar to the results of the study by Okasha and colleagues [11], who reported a cut-off point of 3.8, which had NPV, sensitivity, and accuracy of 86%, 99%, and 96%, respectively, but lower specificity and PPV of 53% and 84%, respectively. Kongkam et al [12] also reported a cut-off point of 3.17, which had lower specificity, sensitivity, PPV, NPV, and accuracy of 66.7%, 86.2%, 89.3%, 60%, and 81.6%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…At present, the five-point scoring system is the main method in the diagnosis of benign and malignant lesions; a higher score is corresponding to a higher elasticity coefficient of a lesion compared to normal tissues 15. In this study, the lesions with no less than 3 points were evaluated as malignant lesions and those with no more than 2 points were evaluated as benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We previously investigated 172 patients identified to have SPL by the previously mentioned noninvasive modalities beside the EUS-FNA to predict the nature of the lesion. [ 3 ] At the cut-off level of 3.8, we had sensitivity, specificity, PPV, NPV, and accuracy of 99%, 53%, 84%, 86%, and 96%, respectively. Then we calculated the best cut-off value to have 7.8 to differentiate between benign and malignant SPL.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, [ 3 ] we evaluated real-time EUS elastography and strain ratio as predictive tools to reach the correct diagnosis for SPL. It had a sensitivity of 98% and specificity of 77% and a diagnostic accuracy of 92%.…”
Section: Introductionmentioning
confidence: 99%